Representations of Feminism In The Drama Series Qalb Al Adala By Walter Parkes And William Finkelstein - Azza Zahra Rafiqah; Bastian Zulyeno; Siti Rohmah Soekarba (IAIN Syekh Nurjati Cirebon, Indonesia, 2023)
Purpose: This study discusses the representation of feminism in the drama series Qalb Al Adala. Qalb Al Adala is an Emirati drama series that follows the perseverance of a woman named Farah in pursuing her career. This series was produced in January 2017 and aired in September 2017. This study aims to explain the representation of feminism and the signs representing feminism in the series. Design/methods/approach: This study uses the qualitative study method along with documentation and literature reviews. The theories applied in this study are the theory of feminism and the semiotic theory of John Fiske, which is based on codes of television. Findings: Results show that Qalb Al Adala represents the values of liberal feminism and existential feminism. The signs representing feminism are depicted through conventional representation with a code of character. On an ideological level, feminist values are represented by the values of liberal feminism and existential feminism.